Determination of Total Flavonoids, Rutin, and Hyperin Contents in the Leaves of Ziziphus Mauritiana Lam. Harvested in Phu Tho - Thi Minh Diep, Nguyen; Thanh Hoa, Ha; Viet Hung, Dao; Thi Xuan Thinh, Ngo; Thi Van Anh, Tran; Thanh Hai, Nguyen; Van Thang, Nguyen; Tuan, Pham Quoc (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
This study developed two quantitative methods. The first one was the photometric method that determined the content of total flavonoids in leaves of Ziziphus mauritiana Lam. and calculated based on rutin, a major compound. The regression equation of the standard sample in the concentration range of 1.0 - 150.0 µg/ml was y = 0.0098x - 0.0096, (R 2 = 0.9994); recovery from 96.48 - 99.81%. The second one was the HPLC-PDA method used for simultaneous quantification of rutin and hyperin, with chromatographic conditions including Phenomenex C18 reversed-phase column (25 × 4.6 cm, 5 µm), a mobile phase solvent system of MeCN (A) - 0.1% formic acid in water (B): isocratic 25% A, 75% B (0-25 minutes); 25-80% A, 75-20% B (25-40 minutes). The column chamber temperature was 30 o C, the flow rate was 0.5 ml/min, and the sample injection volume was 10 µl. The wavelength for simultaneous detection of rutin and hyperin was 354 nm. The limit of detection (LOD) and limit of quantification (LOQ) of rutin and hyperin were 0.05 and 0.165 µg/ml, respectively. Two developed methods were applied to quantify total flavonoids, rutin, and hyperin in several samples of the leaves of Ziziphus mauritiana Lam., which were collected in some districts in Phu Tho province. These methods are simple, fast, and accurate, aiming to serve the standardization of the medicinal material.